(NdINAMIKA MOLEKULQRNYH REAKCIJ (B/s - (NwORONIN(B, (NaNATOLIJ iWANOWI^s; (No[EROW(B, (NwLADIMIR iOSIFOWI^s; (NnIKITIN(B, (Ne(B.(Ne(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 402-419 (775 (NNAZW(B.)s
Keywords: (NfIZI^ESKAQ HIMIQs